Gestión de la empresa Megatec, cantón Chimbo, provincia de Bolívar, periodo 2024-2028. - Estrada Velasco, Edison Paul (2025)
This research work focuses on the management of the Megatec company, located in the La Magdalena Parish of the Chimbo Canton, for the period 2024-2028. Its main objective is to address the problems that have arisen due to the lack of efficient management that allows the company to achieve its organizational goals. In addition, it seeks to respond to the demands of customers, who have expressed dissatisfaction with the quality of the service, especially due to the slowness of the network at certain times of the day, which delays their activities and affects the ability to obtain. To solve these difficulties, a strategic plan is proposed based on the optimization of resources and activities to improve Megatec's management. With this approach, the company is expected to boost its growth and contribute to the economic development of the sector, thus achieving its objectives through the formulation and implementation of long-term strategies and the development of a solid organizational philosophy